Preparation method of chlorine salt conversion film with high corrosion resistance

By preparing a conversion film solution containing manganese chloride and calcium chloride, the surface of magnesium alloy has been nucleated twice, solving the problem of difficult to take into account both the thickness and density of the film layer in the prior art, and achieving low cost and high corrosion resistance The preparation of chloride salt conversion film significantly improves the corrosion resistance of the magnesium alloy surface.

CN119220973AInactive Publication Date: 2024-12-31NORTHEASTERN UNIV CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411133961.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to form a high corrosion-resistant and uniform chloride conversion film on the surface of magnesium alloy at low cost, and it is difficult to take into account the thickness and density of the film layer at the same time, resulting in insufficient corrosion resistance in a strong corrosion environment.

Method used

By preparing a conversion film solution containing manganese chloride, calcium chloride, ammonium dihydrogen phosphate, sodium nitrate and EDTA, the film formation temperature and time are controlled, and the nucleation occurs twice on the surface of the magnesium alloy, and the first nucleation is improved. The thickness of the layer, the second nucleation filling defects, and the self-dense of the film layer is achieved.

Benefits of technology

It has achieved the preparation of a high corrosion resistance conversion film with uniform thickness and dense chloride salt at low cost, significantly improving the corrosion resistance of the magnesium alloy surface, and is suitable for all film layers involving "dissolution-ionization-deposition" systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220973A_ABST
    Figure CN119220973A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a chlorine salt conversion film with high corrosion resistance, which comprises the following steps: dissolving manganese chloride and calcium chloride in water, then adding ammonium dihydrogen phosphate, sodium nitrate and EDTA (Ethylene Diamine Tetraacetic Acid), and carrying out conversion treatment at 50-60 DEG C for 10-15 minutes to obtain a conversion film solution; placing the conversion film solution in a water bath kettle with the temperature of 50-60 DEG C for heating and heat preservation; the magnesium alloy is put into the conversion film solution to form a film for 10-15 min at the film forming temperature of 50-60 DEG C, and a conversion film is formed on the surface of the magnesium alloy; and taking out the magnesium alloy, washing and drying the conversion film, and characterizing. According to the preparation method of the chlorine salt high-corrosion-resistance conversion film, the preparation cost is low, and the prepared film layer is thick and uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal surface corrosion resistance treatment, and in particular to a method for preparing a chloride salt high corrosion resistance conversion film. Background Art

[0002] Magnesium alloys can be widely used in electronic products, military industry, optical instruments, aerospace and other fields due to their good specific strength, specific stiffness, electromagnetic shielding ratio and damping performance. However, due to the poor corrosion resistance of magnesium alloys, surface treatment of magnesium alloys is usually an effective means to improve the corrosion resistance of magnesium alloys. Chemical conversion coatings have become an important means of surface protection for magnesium alloys due to their green and environmentally friendly nature, simple operation and good corrosion resistance. In particular, when magnesium alloys are used in highly corrosive environments, it is even more necessary to prepare a highly corrosion-resistant conversion film on the surface of the magnesium alloy.

[0003] From the perspective of industrial production, how to form a highly corrosion-resistant conversion film on the surface of magnesium alloy at low cost is the focus of current research. In the existing phosphate conversion film technology, the film-forming solution is mainly manganese phosphate. At present, manganese phosphate is mainly manganese sulfate. It is difficult to improve the corrosion resistance of manganese salt conversion film and provide corresponding theoretical guidance. For example, studies have shown that metal ions such as Mg dissolved in magnesium alloy during the film formation process 2+ ,Al 3+ etc. will participate in film formation, but their influence on film deposition has not been studied. Another study pointed out that adding a small amount of Mg to the conversion film solution 2+ , can act as a heterogeneous nucleating agent, reduce the nucleation work, increase the nucleation rate, and improve the corrosion resistance of the film. The fast nucleation rate of the film will reduce the defects of the coating to a certain extent, but it still cannot avoid the defects of the film, and the problems of the primary nucleation itself cannot be solved. Because the energy required for growth is much less than the energy required for nucleation, once the nucleation is formed, it tends to grow, and it is difficult to have a secondary nucleation. Since the defects caused by nucleation cannot be compensated during the growth process, these defects cannot be repaired only by increasing the nucleation rate. The presence of defects will lead to a decrease in the corrosion resistance of the coating. At the same time, due to the limited space for grain growth caused by the fast nucleation rate, the thickness of the film is also difficult to increase. Therefore, it is difficult to form a conversion film with high film thickness and dense and defect-free film at the same time by primary nucleation. However, the thickness of the film and the density of the film are two conditions that must be possessed by a high corrosion-resistant conversion film at the same time.

[0004] Therefore, how to prepare a magnesium alloy conversion film with uniform film layer and high film layer thickness at low cost is an important problem to be solved urgently. If two nucleation processes can be performed during the film formation process, the first nucleation increases the film layer thickness, and the second nucleation fills the defects caused by the first nucleation, the defect problem caused by the first nucleation can be solved, and a conversion film with both film layer thickness and density can be prepared. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a chloride salt high corrosion resistance conversion film with low preparation cost and thick and uniform film layer.

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a chloride salt high corrosion resistance conversion film, comprising the following steps:

[0007] Dissolve manganese chloride and calcium chloride in water, then add ammonium dihydrogen phosphate, sodium nitrate and EDTA and perform conversion treatment at 50-60°C for 10-15 minutes to obtain a conversion coating solution;

[0008] The conversion film solution is placed in a water bath at 50°C-60°C and heated;

[0009] The magnesium alloy is placed in a conversion coating solution and formed at a film forming temperature of 50°C to 60°C for 10 to 15 minutes to form a conversion coating on the surface of the magnesium alloy;

[0010] The magnesium alloy was taken out and the conversion film was washed and dried for characterization.

[0011] Furthermore, in the conversion coating solution, the concentration of manganese chloride is 0.2-0.3 mol / L, the concentration of calcium chloride is 0.2-0.3 mol / L, the concentration of diammonium phosphate is 0.24-0.30 mol / L, the concentration of sodium nitrate is 0.02-0.04 mol / L, and the concentration of EDTA is 0.02-0.05 mol / L.

[0012] Preferably, the film forming temperature is 60°C.

[0013] Preferably, the film forming time is 10 minutes.

[0014] Furthermore, the magnesium alloy is a magnesium alloy block having a size of 30 mm×30 mm×5 mm, 10 mm×10 mm×5 mm or 11 mm×11 mm×12 mm cut by wire cutting.

[0015] Furthermore, the magnesium alloy is polished with 800#, 1000#, and 1200# silica sandpaper and then rinsed and dried with alcohol.

[0016] The present invention provides a method for preparing a chloride salt high corrosion resistance conversion film, in which manganese chloride is used to replace the traditional manganese sulfate when preparing the conversion film solution, and calcium chloride is introduced into the conversion film solution. Different from the current method of relying on different cations generated by metal dissolution to participate in film formation or adding cations of different contents to act as heterogeneous nucleating agents to promote nucleation to increase the nucleation rate of primary nucleation, it is unable to fundamentally solve the defects caused by primary nucleation. From the perspective of theoretical guidance, the present invention quickly screens out the cations required for film formation by calculating the precipitation equilibrium phase diagram, so that nucleation occurs twice in the film formation process, solving the problem that the film defects cannot be repaired during the film deposition process. There are free Mn with different deposition abilities in the solution of the present invention. 2+ , Ca 2+ and the complexed Mn 2+ With Ca 2+ The monohydrogen phosphate can cause two batches of nucleation during the film formation process. The first batch of nucleation can increase the thickness of the film layer. Due to the intense electrochemical reaction at the defect, the pH value and reaction entropy increase, which triggers the second batch of nucleation, so that the second batch of nucleation can target and fill the defect position of the film layer, realize the self-densification of the film layer during the film formation process, and ensure the uniformity and density of the formed conversion film layer.

[0017] The present invention essentially solves the problem caused by one-time nucleation. It is not possible to improve the corrosion resistance of the film layer by simply increasing the nucleation rate. A conversion film that can undergo two nucleations during the film formation process is designed. The present invention provides a solution design idea that is not limited to the field of magnesium alloys and conversion films, but is applicable to all film layers involving the "dissolution-ionization-deposition" system, and can more efficiently and accurately design film-forming solutions and prepare highly corrosion-resistant film layers.

[0018] In addition, the present invention provides a method for preparing a chloride salt high corrosion-resistant conversion film, which controls the film-forming temperature at 50°C-60°C and the film-forming time at 10-15min, which can not only ensure the film-forming effect and film-forming reaction speed of the conversion film solution itself, so that the film layer can fully nucleate and the film layer can be evenly covered, but also promote the full film formation of the conversion film, ensure the thickness of the conversion film, and avoid cracking of the conversion film, so that the formed conversion film has high corrosion resistance.

[0019] At the same time, the present invention provides a method for preparing a chloride salt high corrosion resistance conversion film, and manganese chloride and calcium chloride in the conversion film solution are cheap and easy to obtain, so the preparation cost of the conversion film is relatively low, the economic benefit is high, and it is worthy of promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A flow chart of a method for preparing a chloride salt high corrosion resistance conversion film provided by an embodiment of the present invention;

[0021] Figure 2A precipitation equilibrium phase diagram in a method for preparing a chloride salt high corrosion resistant conversion film provided by an embodiment of the present invention;

[0022] Figure 3 A diagram of the batch nucleation mechanism in a method for preparing a chloride salt high corrosion resistant conversion film provided by an embodiment of the present invention;

[0023] Figure 4 XRD analysis diagrams provided for Comparative Example 1, Comparative Example 2 and Example 1 of the present invention;

[0024] Figure 5 The surface morphology of the conversion film prepared in Comparative Example 2 and Example 1 of the present invention;

[0025] Figure 6 The cross-sectional morphology diagram of the conversion film prepared in Comparative Example 2 and Example 1 of the present invention;

[0026] Figure 7 The Nyquist and Bode diagrams of electrochemical impedance performance of the magnesium alloy or conversion film prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention after being immersed in a 3.5% NaCl solution for 0 h;

[0027] Figure 8 The Nyquist and Bode diagrams of electrochemical impedance performance of the magnesium alloy or conversion film prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention, immersed in a 3.5% NaCl solution for 24 hours;

[0028] Fig. 9 The Nyquist and Bode diagrams of electrochemical impedance performance of the magnesium alloy or conversion film prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention, immersed in a 3.5% NaCl solution for 72 hours;

[0029] Fig.10 The macroscopic corrosion morphologies of the magnesium alloys or conversion films prepared in Comparative Example 1, Comparative Example 2 and Example 1 of the present invention were subjected to neutral salt spray tests for 24 h, 72 h and 120 h, respectively. DETAILED DESCRIPTION

[0030] See also Figure 1 The present invention provides a method for preparing a chloride salt high corrosion resistance conversion film, comprising the following steps:

[0031] Step 1) dissolving manganese chloride and calcium chloride in water, then adding ammonium dihydrogen phosphate, sodium nitrate and EDTA for conversion treatment at 50-60° C. for 10-15 minutes to obtain a conversion coating solution.

[0032] Among them, the concentration of manganese chloride in the conversion film solution is 0.2-0.3 mol / L, the concentration of calcium chloride is 0.2-0.3 mol / L, the concentration of ammonium dihydrogen phosphate is 0.24-0.30 mol / L, the concentration of sodium nitrate is 0.02-0.04 mol / L, and the concentration of EDTA is 0.02-0.05 mol / L.

[0033] The manganese chloride and calcium chloride in the conversion film solution prepared by the present invention are both cheap and easily available, so the preparation cost is relatively low and the economic benefit is high.

[0034] Moreover, the present invention uses cheap and readily available manganese chloride to replace manganese sulfate, and introduces cheap and readily available calcium chloride into the conversion film solution, which not only has low cost and good economic benefits, but also manganese chloride and calcium chloride can promote two batches of nucleation during the film forming process, the first batch of nucleation can increase the thickness of the film layer, and the second batch of nucleation can target and fill the defective positions of the film layer, thereby ensuring the thickness and density of the formed conversion film layer, thereby greatly improving the corrosion resistance of the formed conversion film.

[0035] See Table 1 for the precipitation equilibrium constants of several different film-forming materials. Based on the data in Table 1, the thermodynamic precipitation equilibrium phase diagrams of several film-forming materials can be calculated using the precipitation equilibrium formula, such as Figure 2 shown.

[0036] The present invention designs the conversion film solution from the perspective of the thermodynamic phase diagram of different film-forming substances. It can be seen from the precipitation equilibrium constants of several film-forming substances and the corresponding precipitation equilibrium phase diagrams that the K of MnHPO4 sp The lowest, the easiest to deposit during film formation, followed by CaHPO4, while the K of BaHPO4, SrHPO4 and MgHPO4 sp Relatively large.

[0037] Therefore, the present invention provides a method for preparing a chloride salt high corrosion resistance conversion film, wherein Mn 2+ and Ca 2+ As the main film-forming cation of the conversion film solution. 2+ and Ca 2+ After these two cations, due to the presence of the complexing agent EDTA in the solution, there will be three forms of ions in the solution, namely, free Mn 2+ , Ca 2+ and the complexed Mn 2+ With Ca 2+ , as shown in equations (1) and (2).

[0038]

[0039] Complexed ion Mn 2+ With Ca 2+During the nucleation process, deposition and doping will occur simultaneously, making the Ksp of the complexed (Mn,Ca)HPO4 between MnHPO4 and CaHPO4, such as Figure 3 shown.

[0040] During the film formation process, MnHPO4 with low Ksp preferentially nucleates. As the reaction proceeds, the film formation reaction at the defect is intense, which leads to accelerated hydrogen evolution reaction and significantly increased hydrogen ion consumption, so the pH value at the defect significantly increases (as shown in reaction equations (3)-(4)). At the same time, it promotes the ionization of dihydrogen phosphate to produce more monohydrogen phosphate (as shown in reaction equation (5)). The ion concentration at the defect reaches the Ksp required for the second batch of nucleation, and at this time (Mn,Ca)HPO4 begins the second batch of nucleation (as shown in reaction equation (6)). Therefore, the second batch of nuclei preferentially deposits at the defect, thereby achieving targeted repair of the defects of the film layer. At the same time, since the second batch of nuclei fills the defects of the film layer, the self-densification of the conversion film during the film formation process is achieved.

[0041] Mg-2e→Mg(3)

[0042] H++2e→H(4)

[0043]

[0044]

[0045] Therefore, the present invention selects Mn according to the precipitation equilibrium phase diagram of each film-forming material. 2+ With Ca 2+ As film-forming cations, by controlling the nucleation of different substances in batches, the first nucleation grows first and increases the thickness of the film layer. Subsequently, the second nucleation is deposited at the defects caused by the first nucleation, achieving self-densification of the film layer, thereby increasing the film thickness and density of the conversion film, and thus significantly improving the corrosion resistance of the conversion film.

[0046] Table 1. Precipitation equilibrium constants of various film-forming substances

[0047] substance <![CDATA[MnHPO4]]> <![CDATA[CaHPO4]]> <![CDATA[SrHPO4]]> <![CDATA[BaHPO4]]> <![CDATA[MgHPO4]]> <![CDATA[Ks p ]]> <![CDATA[3.6×10- 8 ]]> <![CDATA[1.0×10- 7 ]]> <![CDATA[2.1×10- 7 ]]> <![CDATA[3.2×10- 7 ]]> <![CDATA[4.3×10- 7 ]]>

[0048] Step 2) The conversion film solution is placed in a water bath at 50-60°C and heated.

[0049] Step 3) placing the magnesium alloy in a conversion coating solution and forming a film at a film forming temperature of 50-60° C. for 10-15 minutes to form a conversion film on the surface of the magnesium alloy.

[0050] The magnesium alloy is cut into magnesium alloy blocks of 30 mm×30 mm×5 mm, 10 mm×10 mm×5 mm or 11 mm×11 mm×12 mm in size by wire cutting.

[0051] In addition, after the magnesium alloy is cut into blocks, the surface oxide layer of the magnesium alloy is polished with 800#, 1000#, and 1200# silica sandpaper in turn, and then rinsed with alcohol and blown dry for use.

[0052] Among them, if the film forming temperature is lower than 50°C, the film forming reaction speed will be slow and it is easy to cause less film nucleation and uneven film coverage, resulting in poor corrosion resistance of the conversion film. However, if the film forming temperature is higher than 60°C, since the conversion film solution itself is in an oversaturated state, the high temperature will cause the conversion film solution to decompose and fail, affecting film formation. Therefore, in the film forming process of magnesium alloy, controlling the film forming temperature at 50°C-60°C can not only ensure the film forming effect and film forming reaction speed of the conversion film solution itself, so that the film layer can fully nucleate and evenly cover the film layer, but also promote the full film formation of the conversion film, ensure the film thickness of the conversion film, and ensure the density of the film layer, so that the film layer has higher corrosion resistance.

[0053] For the film-forming time, if the film-forming time is less than 10 minutes, the film-forming time is short and the film thickness is thin. However, if the film-forming time is more than 15 minutes, it is difficult to further increase the film thickness, which will affect the film-forming efficiency and the formed film is prone to cracking. Therefore, controlling the film-forming time can not only ensure the thickness of the film and avoid cracking of the conversion film, but also enable the film to fully nucleate, ensure the uniformity of the film, and ensure the density of the film, so that the formed conversion film has high corrosion resistance.

[0054] As a best embodiment of the present invention, the best film-forming temperature of the magnesium alloy in the conversion coating solution is 60°C.

[0055] Furthermore, as a best specific embodiment of the present invention, the best film-forming time of the magnesium alloy in the conversion coating solution is 10 minutes.

[0056] Step 4) After the magnesium alloy film is formed, the magnesium alloy is taken out and the conversion film on its surface is rinsed with deionized water and dried in the air. Subsequent characterization is performed after 10 to 15 hours.

[0057] The following is a specific description of the preparation method of a chloride salt high corrosion resistance conversion film provided by the present invention through comparative examples and examples.

[0058] Comparative Example 1

[0059] In this comparative example, only a magnesium alloy matrix is ​​prepared without performing a conversion treatment on the magnesium alloy matrix.

[0060] (1) The magnesium alloy was cut into pieces of 30 mm × 30 mm × 5 mm in size using wire cutting for characterization of morphology and corrosion resistance testing.

[0061] (2) Grind the sample with 800#, 1000#, and 1200# silica sandpaper in turn, and rinse and dry with alcohol.

[0062] The XRD phase analysis results of the magnesium alloy of Comparative Example 1 of the present invention are as follows: Figure 4 shown.

[0063] In order to characterize the electrochemical impedance performance of the magnesium alloy conversion film of Comparative Example 1, the magnesium alloy obtained in Comparative Example 1 was immersed in a 3.5% NaCl solution, and the electrochemical impedance performance of the magnesium alloy was characterized by immersion for different time periods. The Nyquist plot of the magnesium alloy obtained in Comparative Example 1 after being immersed in a 3.5% NaCl solution for 0 h is shown in FIG. Figure 7 As shown in (a), the Bode plot obtained after immersion in 3.5% NaCl solution for 0 h is shown in Figure 7 (b) As shown; the Nyquist diagram of the magnesium alloy obtained in Comparative Example 1 was obtained by immersing it in a 3.5% NaCl solution for 24 h. Figure 8 (c) shows the Bode diagram obtained by immersing in 3.5% NaCl solution for 24 h. Figure 8 (d) As shown; the Nyquist diagram of the magnesium alloy obtained in Comparative Example 1 was obtained by immersing it in a 3.5% NaCl solution for 72h. Fig. 9 As shown in (e), the Bode diagram obtained by immersing in 3.5% NaCl solution for 72 hours is as follows Fig. 9 (f) as shown.

[0064] In order to evaluate the long-term corrosion resistance of the magnesium alloy of Comparative Example 1, a neutral salt spray test was performed on the magnesium alloy of Comparative Example 1. The macroscopic corrosion morphology of the conversion film after 24h, 72h and 120h of neutral salt spray test is shown in the following figure: Fig.10 shown.

[0065] Comparative Example 2

[0066] In this comparative example, the magnesium alloy substrate is prepared and then subjected to ordinary conversion treatment.

[0067] (1) The magnesium alloy was cut into pieces of 30 mm × 30 mm × 5 mm in size using wire cutting for characterization of morphology and corrosion resistance testing.

[0068] (2) Grind the sample with 800#, 1000#, and 1200# silica sandpaper in turn, and rinse and dry with alcohol.

[0069] (3) Chemical conversion treatment: 0.25 mol / L manganese sulfate was dissolved in water, and then 0.27 mol / L diammonium phosphate, 0.03 mol / L sodium nitrate and 0.04 mol / L EDTA were added, and the conversion treatment was carried out at 60°C for 10 min.

[0070] (4) Place the above solution in a water bath at 60°C.

[0071] (5) The magnesium alloy is placed in the above-mentioned heated conversion coating solution and the film is formed for 10 minutes.

[0072] (6) Take out the sample, rinse it with deionized water, and dry it in air. Characterize it after 12 hours.

[0073] The XRD phase analysis results of the magnesium alloy conversion film prepared in Comparative Example 2 of the present invention are as follows: Figure 4 shown.

[0074] The surface morphology of the magnesium alloy conversion film obtained in Comparative Example 2 of the present invention is as follows: Figure 5 (a) shows the cross-sectional morphology of the magnesium alloy conversion film obtained in Comparative Example 2. Figure 6 (a) shown.

[0075] In order to characterize the electrochemical impedance performance of the conversion film of the magnesium alloy obtained in Comparative Example 2, the magnesium alloy with the surface film obtained in Comparative Example 2 was immersed in a 3.5% NaCl solution, and the electrochemical impedance performance of the conversion film on its surface was characterized by immersion for different time periods. The Nyquist plot of the conversion film of the magnesium alloy obtained in Comparative Example 2 immersed in a 3.5% NaCl solution for 0 h is shown in FIG. Figure 7 As shown in (a), the Bode plot obtained after immersion in 3.5% NaCl solution for 0 h is shown in Figure 7 (b) As shown; the conversion film of the magnesium alloy obtained in Comparative Example 2 was immersed in a 3.5% NaCl solution for 24h to obtain the Nyquist diagram as shown Figure 8 (c) shows the Bode diagram obtained by immersing in 3.5% NaCl solution for 24 h. Figure 8 (d) As shown; The conversion film of the magnesium alloy obtained in Comparative Example 2 was immersed in a 3.5% NaCl solution for 72h to obtain the Nyquist diagram as shown Fig. 9 As shown in (e), the Bode diagram obtained by immersing in 3.5% NaCl solution for 72 hours is as follows Fig. 9 (f) as shown.

[0076] In order to evaluate the long-term corrosion resistance of the magnesium alloy conversion film of Comparative Example 2, a neutral salt spray test was performed on the conversion film on the surface of the magnesium alloy of Comparative Example 2. The macroscopic corrosion morphology of the conversion film after 24h, 72h and 120h of neutral salt spray test is shown in the following figure: Fig.10 shown.

[0077] Example 1

[0078] The present embodiment provides a method for preparing a chloride salt high corrosion resistance conversion film, comprising the following steps:

[0079] (1) The magnesium alloy was cut into pieces of 30 mm × 30 mm × 5 mm in size using wire cutting for characterization of morphology and corrosion resistance testing.

[0080] (2) Grind the sample with 800#, 1000#, and 1200# silica sandpaper in turn, and rinse and dry with alcohol.

[0081] (3) Chemical conversion treatment: 0.25 mol / L manganese chloride and 0.25 mol / L calcium chloride were dissolved in water, and then 0.27 mol / L diammonium phosphate, 0.03 mol / L sodium nitrate and 0.04 mol / L EDTA were added and the conversion treatment was carried out at 60°C for 10 min.

[0082] (4) Place the above solution in a water bath at 60°C.

[0083] (5) The magnesium alloy is placed in the above-mentioned heated conversion coating solution and the film is formed for 10 minutes.

[0084] (6) Take out the sample, rinse it with deionized water, and dry it in air. Characterize it after 12 hours.

[0085] The XRD phase analysis results of the magnesium alloy conversion film prepared in Example 1 of the present invention are as follows: Figure 4 shown.

[0086] from Figure 4 It can be seen that the diffraction peaks of the magnesium alloy matrix and the second phase are mainly present in Comparative Example 1, while in Comparative Example 2, in addition to the diffraction peaks of the magnesium alloy matrix and the second phase, there are also the main components of the conversion film layer, MgHPO4 and MnHPO4. In addition to the diffraction peaks of the second phase, Example 1 also has a left-shifted MnHPO4 peak, which is due to the Ca 2+ Doped in the lattice of MnHPO4, replacing Mn 2+ The sites of the second batch of nuclei are formed, resulting in lattice expansion, which is the main component of the second batch of nuclei. This result shows that the present embodiment 1 is a batch nucleation, which can effectively improve the film thickness and uniformity, thereby improving the corrosion resistance of the conversion film.

[0087] The surface morphology of the magnesium alloy conversion film prepared in Example 1 of the present invention is as follows: Figure 5 As shown in (b), the cross-sectional morphology of the magnesium alloy conversion film prepared in Example 1 of the present invention is as follows Figure 6 (b) as shown.

[0088] from Figure 5 It can be seen that for Comparative Example 2, the film-forming cations are only Mn 2+When the number of nuclei is large, it is difficult for the nuclei to grow, which results in a smaller grain size of the film structure. For Example 1, due to the low equilibrium constant of MnHPO4 precipitation, it preferentially nucleates and grows. 2+ After that, Ca 2+ With Mn 2+ Doping occurs, which causes the precipitation equilibrium constant to be between Mn and Ca. As the pH increases during the reaction, a second batch of nucleation occurs to form small grains, and eventually a structure in which large and small grains coexist is formed. The small grains fill the defects of the film layer, thereby ensuring the uniformity of the conversion film layer.

[0089] from Figure 6 It can be seen that the film thickness of the conversion film cross section of Comparative Example 2 is about 10 μm, and the film thickness is uneven, and the outer film has relatively weak areas. The film thickness of the conversion film cross section of Example 1 is uniform and the film thickness increases, and the overall film thickness is about 15-20 μm.

[0090] Therefore, Example 1 of the present invention effectively improves the film thickness and uniformity by controlling batch nucleation, thereby improving the corrosion resistance of the conversion film.

[0091] In order to characterize the electrochemical impedance performance of the conversion film of the magnesium alloy of Example 1, the magnesium alloy with the surface film obtained in Example 1 of the present invention was immersed in a 3.5% NaCl solution, and the electrochemical impedance performance of the conversion film on its surface was characterized by immersion for different time periods. The Nyquist plot of the conversion film of the magnesium alloy obtained in Example 1 immersed in a 3.5% NaCl solution for 0 h is shown in FIG. Figure 7 As shown in (a), the Bode plot obtained after immersion in 3.5% NaCl solution for 0 h is shown in Figure 7 (b) As shown; the Nyquist diagram of the conversion film of the magnesium alloy obtained in Example 1 was obtained by immersing it in a 3.5% NaCl solution for 24 hours. Figure 8 (c) shows the Bode diagram obtained by immersing in 3.5% NaCl solution for 24 h. Figure 8 (d) As shown; The Nyquist diagram of the conversion film of the magnesium alloy obtained in Example 1 was obtained by immersing it in a 3.5% NaCl solution for 72h. Fig. 9 As shown in (e), the Bode diagram obtained by immersing in 3.5% NaCl solution for 72 hours is as follows Fig. 9 (f) as shown.

[0092] The value of impedance modulus represents the level of corrosion resistance. Figure 7 (a) and Figure 7(b) It can be seen that at the beginning of immersion, the high-frequency capacitive reactance arc of the magnesium alloys of Comparative Example 2 and Example 1 after chemical conversion treatment increases, among which the capacitive reactance arc of Example 1 is the largest. In addition, the modulus value |Z| of Example 1 0.01Hz Compared with the modulus value |Z| of comparative example 2 0.01Hz Compared with the previous study, the 2 ), the result shows that the corrosion resistance of Example 1 is higher than that of Comparative Example 2. Moreover, as the immersion time increases, see Figure 8 (c) and Figure 8 (d) After immersion for 24 h, although the modulus of Example 1 decreased to 11091 (Ω·cm 2 ), but still higher than the modulus value of comparative example 2, indicating that the corrosion resistance of Example 1 is slightly reduced under long-term immersion, but still higher than that of comparative example 2. Fig. 9 (e) and Fig. 9 (f) After immersion for 72 hours, the impedance modulus of Example 1 is still 3 times that of Comparative Example 2, and still has good corrosion resistance.

[0093] In order to evaluate the long-term corrosion resistance of the magnesium alloy conversion film of Example 1, a neutral salt spray test was performed on the conversion film on the surface of the magnesium alloy of Example 1. The macroscopic corrosion morphology of the conversion film after 24h, 72h and 120h of neutral salt spray test is shown in the following figure: Fig.10 shown.

[0094] from Fig.10 It can be seen that after 24 hours of salt spray test, only a small amount of corrosion occurs on the edge of the conversion film of Example 1, and no corrosion occurs on the surface, while many corrosion spots appear in Comparative Example 1 and Comparative Example 2. After 120 hours of salt spray test, only a small amount of corrosion spots appear on the surface of the conversion film of Example 1, and the corrosion products of Comparative Example 1 almost cover the surface, while the number of corrosion spots increases in Comparative Example 2, which shows that the corrosion resistance of the magnesium alloy conversion film prepared in Example 1 of the present invention is much higher than that of the traditional conversion film.

[0095] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a chloride salt high corrosion resistance conversion film, characterized in that: The steps include: Dissolve manganese chloride and calcium chloride in water, then add ammonium dihydrogen phosphate, sodium nitrate and EDTA and perform conversion treatment at 50-60°C for 10-15 minutes to obtain a conversion coating solution; The conversion film solution is placed in a water bath at 50°C-60°C and heated; The magnesium alloy is placed in a conversion coating solution and formed at a film forming temperature of 50°C to 60°C for 10 to 15 minutes to form a conversion coating on the surface of the magnesium alloy; The magnesium alloy was taken out and the conversion film was washed and dried for characterization.

2. The method for preparing a chloride salt high corrosion resistance conversion film according to claim 1, characterized in that: The concentration of manganese chloride in the conversion coating solution is 0.2-0.3 mol / L, the concentration of calcium chloride is 0.2-0.3 mol / L, the concentration of ammonium dihydrogen phosphate is 0.24-0.30 mol / L, the concentration of sodium nitrate is 0.02-0.04 mol / L, and the concentration of EDTA is 0.02-0.05 mol / L.

3. The method for preparing a chloride salt high corrosion resistance conversion film according to claim 1, characterized in that: The film forming temperature is 60°C.

4. The method for preparing a chloride salt high corrosion resistance conversion film according to claim 3, characterized in that: The film forming time is 10 minutes.

5. The method for preparing a chloride salt high corrosion resistance conversion film according to claim 1, characterized in that: The magnesium alloy is a magnesium alloy block having a size of 30 mm×30 mm×5 mm, 10 mm×10 mm×5 mm or 11 mm×11 mm×12 mm cut by wire cutting.

6. The method for preparing a chloride salt high corrosion resistance conversion film according to claim 5, characterized in that: The magnesium alloy was polished with 800#, 1000#, and 1200# silicon dioxide sandpaper and then rinsed and dried with alcohol.

Citation Information

Cited By

  • Preparation method of chemical conversion coating on surface of metal alloy matrix

    CN120231041A